Teaching Grammar for Contemporary Generations at Cendekia Al-Ruwaq Al-Azhar Al-Sharif Secondary School, Pandan Duri, East Lombok, for the academic year 2022-2023 - Nasirin, Nasirin; Supriadi, Lalu; Wahyudin, Dedi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study investigates grammar education for contemporary generations at Cendekia Al-Ruwaq Al-Azhar Al-Sharif Secondary School, Pandan Duri, East Lombok, during the academic year 2022-2023. The objectives are to assess the teaching practices and identify challenges and solutions encountered in teaching grammar to contemporary generations at this institution. Employing a descriptive qualitative approach, data was collected through observation, interviews, and documentation. Observations focused on teaching activities at Cendekia Al-Ruwaq Al-Azhar Al-Sharif Secondary School, while interviews provided insights into the teaching of grammar. Documentation aided in acquiring information about the school's context. Results highlight teaching practices and challenges faced at Cendekia Al-Ruwaq Al-Azhar Al-Sharif Secondary School, Pandan Duri, East Lombok. This research underscores the importance of addressing contemporary educational needs in grammar instruction.